USING PAPER WASTE AS ADSORBENT FOR METHYL VIOLET DYE REMOVAL FROM WASTE WATER - Besma Mohammed Fahad; Nisreen Sabah Ali; Tamarah Tareq Hameed (Journal of Engineering and Sustainable Development, 2018)
This study has been conducted to examine the possibility of using waste paper as an adsorbent to remove methyl violet (MV) 2B dye from waste water. Initial dye concentration in the rang (20 to 80mg/L), pH of solution in the rang (4-10), adsorbent dose range (0.5-2.5 g) and contact time varying from (30 to 180)min, were studied. The experimental adsorption isotherms were fitted with the Langmuir and Freundlich models were found to be more represented to the experiments with high correlation coefficient (R2 = 0.8144). The results showed that the highest (MV ) dye removal efficiency was (97.63) at optimization condition pH 8, at room temperature for 120min, 2 g adsorbent dose and 20 mg/L dye concentration. The value of adsorption capacity was found to be 4.3 mg /g.